Mitochondrial DNA oxidation and content in different metabolic phenotypes of women with polycystic ovary syndrome - Mailén Rojo; Mailén Rojo; Hernán Pérez; Hernán Pérez; Andrea Liliana Millán; Andrea Liliana Millán; María Constanza Pautasso; Alejandra Duarte; Alejandra Duarte; Giselle Adriana Abruzzese; Alicia Beatriz Motta; Alicia Beatriz Motta; et al. (Frontiers in Endocrinology)
IntroductionPolycystic Ovary Syndrome (PCOS) affects 5-20% of reproductive-aged women. Insulin resistance (IR) is common in PCOS with consequent elevated risks of metabolic disorders and cardiovascular mortality. PCOS and obesity are complex conditions associated with Metabolic Syndrome (MS), contributing to cardiovascular disease and type 2 diabetes mellitus (T2D). Obesity and PCOS exacerbate each other, with central obesity driving metabolic changes. Mitochondrial dysfunction, characterized by oxidative stress and reduced antioxidant capacity, plays a key role in PCOS pathology.MethodsIn our study, we investigated 81 women with PCOS, and 57 control women aged 16 to 46 years old. Relative mitochondrial DNA (mtDNA) content and its oxidation level (8-oxoguanine, 8-OxoG) were determined in peripheral blood leukocytes by the SYBR Green method real-time PCR.ResultsOur findings showed that patients with PCOS had decreased mtDNA content and increased oxidation damage. Stratifying these patients by metabolic profile, revealed a progressive decline in mtDNA content from the normal-weight control group to the MHO-PCOS and MUO-PCOS groups, suggesting that lower mtDNA content is linked to obesity and worse metabolic profile. However, mtDNA oxidation levels did not differ significantly among these groups. Additionally, the decline in mtDNA content and the increase in oxidation levels between controls and patients with PCOS lost significance when these relationships were adjusted for the HOMA index.DiscussionThis finding suggests that IR could be the main factor contributing to mitochondrial dysfunction in PCOS. Maintaining optimal mtDNA copies are crucial for mitochondrial and cell function, suggesting potential therapeutic targets for PCOS-associated metabolic disturbances.